2016
DOI: 10.1007/82_2016_497
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Staphylococcus aureus Nasal Carriage Patterns in the Community

Abstract: Staphylococcus aureus (S. aureus) is a Gram-positive opportunistic pathogen that colonizes frequently and asymptomatically the anterior nares of humans and animals. It can cause different kinds of infections and is considered to be an important nosocomial pathogen. Nasal carriage of S. aureus can be permanent or intermittent and may build the reservoir for autogenous infections and cross-transmission to other individuals. Most of the studies on the epidemiology of S. aureus performed in the past were focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 131 publications
3
52
1
7
Order By: Relevance
“…Young age and male gender are among a range of factors sometimes considered to increase the carriage of S. aureus carriage in the community, although mixed results have been observed [20,29]. While these factors may affect carriage rates, this study found no evidence that gender is a factor that contributes to the chance of having a S. aureus positive DFI.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Young age and male gender are among a range of factors sometimes considered to increase the carriage of S. aureus carriage in the community, although mixed results have been observed [20,29]. While these factors may affect carriage rates, this study found no evidence that gender is a factor that contributes to the chance of having a S. aureus positive DFI.…”
Section: Discussioncontrasting
confidence: 70%
“…This study therefore suggests that the rate of S. aureus positive DFIs may be independent of these factors, however these findings are somewhat limited by the statistical power. In general, the prevalence of commensal S. aureus colonisation is considered to decline with increasing age, including among hospital patients [20,29]. However, this study found that the prevalence of S. aureus in DFIs was in fact associated with increasing patient age.…”
Section: Discussionmentioning
confidence: 54%
“…In our population of university students, which belongs to different nationalities, the nasal S. aureus carriage rate was 30.9%, and the MRSA carriage rate was 11.3%. S. aureus nasal carriage rates remarkably vary among different populations; however, our rates are comparable with other reports with similar study samples [16][17][18] . Studies focusing on university students have reported MRSA prevalence in a range between 1.5% and 13% [18][19][20][21][22] .…”
Section: Discussionsupporting
confidence: 90%
“…S. aureus carrier state can be permanent (applies to 6-37%, on average 20% of the population) or transient (9-70%, an average of 30%), and asymptomatic S. aureus colonization never occurs in about 50% (in the range from 2 to 73%) of healthy adults (17,18). S. aureus most often inhabits the mucous membrane of the nasal cavity (10-48% of carriers) and throat (4-64%), gastrointestinal tract (17-31%) and skin on which it particularly prefers warm and moist places, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nosicielstwo S. aureus może mieć charakter stały (dotyczy 6 -37%, średnio 20% populacji) lub przejściowy (9 -70%, średnio 30%), a u około 50% (w zakresie od 2 do 73%) zdrowych, dorosłych osób bezobjawowa kolonizacja S. aureus nigdy nie występuje (17,18). Gronkowiec złocisty u nosicieli najczęściej zasiedla błonę śluzową jamy nosowej (10 -48% nosicieli) oraz gardła (4 -64%), przewód pokarmowy (17 -31%) oraz skórę, na której szczególnie preferuje miejsca ciepłe i wilgotne, czyli skórę pach (około 8%), pachwin (nawet do 63%), okolic klatki piersiowej, brzucha (15%) oraz krocza (około 22%) (19).…”
Section: Dyskusjaunclassified